Further Evidence of the Association of the Diacylglycerol Kinase Kappa (DGKK) Gene With Hypospadias - Hozyasz, Kamil Konrad; Mostowska, Adrianna; Kowal, Andrzej; Mydlak, Dariusz; Tsibulski, Alexander; Jagodzi?ski, Pawe? P. (Urology Journal, 2018)
Purpose: Hypospadias is a common developmental anomaly of the male external genitalia. In previous studies conducted on West European, Californian, and Han Chinese populations the relationship between polymorphic variants of the diacylglycerol kinase kappa (DGKK) gene and hypospadias have been reported. The aim was to study the possible associations between polymorphic variants of the DGKK gene and hypospadias using an independent sample of the Polish population. Materials and Methods: Ten single nucleotide polymorphisms in DGKK, which were reported to have an impact on the risk of hypospadias in other populations, were genotyped using high-resolution melting curve analysis in a group of 166 boys with isolated anterior (66%) and middle (34%) forms of hypospadias and 285 properly matched controls without congenital anomalies. Results: Two DGKK variants rs11091748 and rs12171755 were associated with increased risk of hypospadias in the Polish population. These results were statistically significant, even after applying the Bonferroni correction for multiple comparisons (P < .005). All the tested nucleotide variants were involved in haplotype combinations associated with hypospadias. The global p-values for haplotypes comprising of rs4143304-rs11091748, rs11091748-rs17328236, rs1934179-rs4554617, rs1934183-rs1934179-rs4554617 and rs12171755-rs1934183-rs1934179- rs4554617 were statistically significant, even after the permutation test correction. Conclusion: Our study provides strong evidence of an association between DGKK nucleotide variants, haplotypes and hypospadias susceptibility.